PROBLEMS OF DOMESTIC EXPORTERS IN WARTIME CONDITIONS - Verbytska , H.L. (The actual problems of regional economy development, 2023)
The purpose of the study is to study the applied problems of domestic exporters in wartime conditions. The research used scientific methods of induction and deduction, analysis and synthesis, comparison, analytical and structural-logical. The results of the study showed that Russian military aggression caused a number of problems for Ukrainian exporters in various sectors of the economy, moreover, it put entire industries on the verge of survival. A detailed analysis of the dynamics and structure of exports by the main sectors of the economy was carried out. The main threats faced by them in this difficult time for our entire state have been identified. A conclusion is formulated regarding the need for innovative modernization of the post-war economy of Ukraine as a basis for economic development. The main tasks of which will be the structural restructuring of the Ukrainian economy and the development of high-tech export-oriented industries. At the same time, the state's efforts should be focused on determining the possibilities of reorienting the efforts of entrepreneurs to innovative activities, overcoming the technological lag behind developed countries. In the opposite case, the presence of the Ukrainian economy on the periphery of world information and financial processes will cause the "washing out" of national wealth through the mechanism of non-equivalent exchange, the loss of its own sources of economic growth in the long term. The scientific novelty of the study consists in the use of a complex approach to the justification of ways to improve the export policy of Ukraine in the post-war period, the implementation of which will allow Ukrainian producers to occupy a prominent place in the international division of labor. The priority directions for improving the export policy of Ukraine in the post-war period are: development of innovative activities; successive restructuring of the commodity structure of export and import by bringing it closer to the structural ratios characteristic of countries with a market economy, namely reducing the share of raw materials in favor of high-tech ones; increasing the competitiveness of products thanks to the use of the latest marketing tools.